Comportamiento agronómico del cultivo de acelga (Beta vulgaris L.) con diferentes abonos orgánicos en la finca experimental La María, año 2014 - Meléndez Vega, Néstor Daniel (2015)
In this paper the agronomic performance of the beet crop (Betavulgaris L.) with different organic fertilizers were evaluated "in the Experimental farm La Maria, UTEQ. Year 2014, with the use of organic manure and water hyacinth vermicompost with three different doses respectively per subscription using a completely randomized design with 7 treatments and four repetitions. At 15, the vegetative development of the plant was evaluated 30y 45 days with reference to plant height, leaf length, number of leaves and leaf width and 65, 85, 105Y 125 days harvest was evaluated number of sheets harvested and weight of leaves per treatment. According to Tukey (P ≥ 0.05) The variance analysis shows that with the addition of humus in the four crops T2 (hl 3kg / m2) reach a weight of 30 kg leaves harvested the best answer regarding other treatments, while T1 (hl 1kg / m2 11.18 kg had the lowest performance Achieving better results with T2 vermicompost doses of 3 kg / m2 80